Characteristics of Fried Milk Made of Cows Milk by Using of Papain as a Coagulant - Yakob Robert Noach; Angelina Yutami Mayavanti; Heri Armadianto (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2023)
This research aims to determine the effect of the use of papain as a coagulant on physical and organoleptic of fried milk made of cows milk. The Completely Randomized Design (CRD) with 4 treatments and 4 replication was applied in this experiment. Those treatment were papain levels tested consist: P1: 0.5% of milk volume, P2: 1% of milk volume, P3: 1.5% of milk volume and P4: 2% of milk volume. Variables measured were curd yield, fried milk yield, density, pH, color, taste, aroma and texture. The results showed that the treatment had a significant effect (P<0.05) on curd yield, density, pH and texture of fried milk and had no significant effect (P>0.05) on fried milk yield, color, taste and aroma. It can be concluded that increasing of papain level can decreased curd yield and density, increasing of fried milk yield, pH and smoother in texture,but stabilized in color, taste and aroma of fried milk. The best results found at the use of papain as much as 0.5% (P1) .